Securin Enhances the Anti-Cancer Effects of 6-Methoxy-3-(3′,4′,5′-Trimethoxy-Benzoyl)-1H-Indole (BPR0L075) in Human Colorectal Cancer Cells - Tseng, Ho-Hsing; Chuah, Qiu-Yu; Yang, Pei-Ming; Chen, Chiung-Tong; Chao, Jung-Chi; Lin, Ming-Der; Chiu, Shu-Jun (PLOS ONE, 2012)
BPR0L075 [6-methoxy-3-(3′,4′,5′-trimethoxy-benzoyl)-1H-indole] is a novel anti-microtubule drug with anti-tumor and anti-angiogenic activities in vitro and in vivo. Securin is required for genome stability, and is expressed abundantly in most cancer cells, promoting cell proliferation and tumorigenesis. In this study, we found that BPR0L075 efficiently induced cell death of HCT116 human colorectal cancer cells that have higher expression levels of securin. The cytotoxicity of BPR0L075 was attenuated in isogenic securin-null HCT116 cells. BPR0L075 induced DNA damage response, G2/M arrest, and activation of the spindle assembly checkpoint in HCT116 cells. Interestingly, BPR0L075 induced phosphorylation of securin. BPR0L075 withdrawal resulted in degradation of securin, mitotic exit, and mitotic catastrophe, which were attenuated in securin-null cells. Inhibition of cdc2 decreased securin phosphorylation, G2/M arrest and cell death induced by BPR0L075. Moreover, BPR0L075 caused cell death through a caspase-independent mechanism and activation of JNK and p38 MAPK pathways. These findings provided evidence for the first time that BPR0L075 treatment is beneficial for the treatment of human colorectal tumors with higher levels of securin. Thus, we suggest that the expression levels of securin may be a predictive factor for application in anti-cancer therapy with BPR0L075 in human cancer cells.